2015
DOI: 10.14252/foodsafetyfscj.2015018
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Excess Monitoring for Beef after the Fukushima Accident

Abstract: Herein we analyzed food monitoring data regarding the Fukushima accident. The Japanese government ordered local governments to implement food monitoring after the Fukushima nuclear accident. This protective action for food safety contributed to the reduction of internal radiation exposure derived from the Fukushima accident. According to the food monitoring data collected from March 2011 to March 2015, more than 70% of the samples were beef. One hundred fifty four samples from a total of 776,310 beef samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The first occupational fatality following the start of emergency work occurred on May 14, 2011, with myocardial infarction being the cause of death. Multiple studies have reported the implementation of work site health management for the prevention of diseases among workers at the Fukushima Daiichi Nuclear Power Plant 6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…The first occupational fatality following the start of emergency work occurred on May 14, 2011, with myocardial infarction being the cause of death. Multiple studies have reported the implementation of work site health management for the prevention of diseases among workers at the Fukushima Daiichi Nuclear Power Plant 6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…The Ministry of Health, Labor, and Welfare (MHLW) as the risk manager, under the recommendation of the Nuclear Emergency Commission led by the Prime Minister, responded quickly by establishing a regulation that stipulates the provisional regulatory limits of radioactive contaminants in foods. These regulatory limits were adopted from the "index relating to limits on food and drink ingestion" of the Nuclear Safety Commission (NSC) of Japan (Shimura, Yamaguchi, Terada, Yunokawa, et al 2015). This quick response was aimed at reducing the potential risk of internal exposure to radioactively contaminated foods and at the same time recovering public trust, which was at the time on a very low level (Reiher 2016).…”
Section: Japanmentioning
confidence: 99%